Peran Dinas Kebudayaan Dan Pariwisata Kota Tanjungpinang Dalam Ajang Anugerah Desa Wisata Indonesia (ADWI) Studi Kasus: Pulau Penyengat Kota Tanjungpinang - Diah Ayu Sholeha; Desma Tri Anggriani; Mellyana Candra (Lembaga Pengembangan Kinerja Dosen, 2024)
Penyengat Island is included in the cultural tourism destinations in Tanjungpinang City, which is located in Tanjungpinang District, Riau Islands Province. There is a very strong religious tourism on Penyengat Island, one of which is pilgrimage tourism. Penyengat Island also has heritage buildings from the Riau Lingga Kingdom, Malay arts, gurindam 12, and customs that are still strong in their authenticity. The aim of this research is to look at the role, challenges and follow-up of the Tanjungpinang City Culture and Tourism Department in winning Penyengat Island at the